Comparative Evaluation of Parabolic Collector and Scheffler Reflector For Solar Cooking - Jatinra khan (International Journal of Science and Society, 2021)
Solar energy is transforming to be the promising renewable energy resource that could be used efficiently for human basic needs like cooking. This study presents the performance analysis of solar cooking instruments based on their geometrical aspects. The main aim is to find the best solar cooking device that can efficiently absorb heat reflecting from its surface. Here we evaluated the performance of parabolic type solar reflector and Scheffler type solar reflector in terms of its thermal efficiency and losses. The main dependent factor for this comparative analysis is the geometry of the reflectors with a diameter of 1.5 m and the radiation of the sun. For better reflectivity in both receiver and concentrator or reflector medium, stainless steel material is used. Depending on these factors, we have evaluated performance of both the reflectors and found satisfactory results. Theoretical and simulated results over various conditions prove that the Scheffler reflector performs well compared to parabolic collector.